(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
In the workshop on Diplomatic correspondences in the Italian Renaissance, directed in January-May 2018 by Francesco Storti and Francesco Senatore in the Istituto italiano per gli studi filosofici of Naples, 12 undergraduate and graduate students learned to read and trascribe italian diplomatic dispatches of the 15th cent., producing a specimen of scientific edition. In the opinion of the author, such activities and similar ones are very useful for future school teachers and scholars and they could be introduced in the university and pHD courses of history. Students of humanistic sciences should have concrete contacts with the historical research on primary sources. On the other hand, editing of historical sources could become a marginal activity because it is not enough appreciated in the current research evaluation processes. DOI 10.17464/9788867743360